Non-aqueous electrowetting liquid lens with centimeter-level large aperture based on dielectric failure suppression principle - You-Ran Zhao; Zhao-Song Li; Yi Zheng; Di Wang; Xiao-Ke Lu; Yu-Cheng Lin; Hao-Ran Zhang; Chao Liu; Qiong-Hua Wang (Light: Science & Applications)
Abstract Liquid lens offers a novel approach to achieving large depth of field, wide viewing angle, high speed, and high-quality imaging in zoom optical systems. However, the aperture and reliability limit the lens’s performance in various optical applications. The liquid material is crucial for the reliability of the large-aperture liquid lens. To solve the dielectric failure problem associated with the large aperture, we first reveal the mechanism of dielectric failure based on the transport properties of electrolyte solutions and the impact of electrochemical reaction rates from physical chemistry so as to propose a theoretical method to suppress dielectric failure fundamentally. Based on this theory, we develop a series of non-aqueous organic solutions to suppress high-voltage dielectric failure. Next, we identify the optimal formulation for comprehensive optical performance and fabricate a centimeter-level large-aperture electrowetting liquid lens. This lens features an optical power variation range of −11.98 m−1 to 12.93 m−1, with clear and high-quality imaging function, which can enlarge the field of view and depth adjustment range of holographic reconstructions while maintaining excellent edge clarity of the reconstructed images. The proposed centimeter-level large-aperture non-aqueous electrowetting liquid lens effectively suppresses dielectric failure under high voltage, demonstrates excellent optical performance, and holds exciting potential for applications in 3D display, precision measurement, biomedical observation, and more.